TASK BASED LANGUAGE LEARNING - Kuzmina Minnur Kuzminichna (Modern American Journals, 2026)
Task-Based Language Learning (TBLL) is a pedagogical approach that organizes instruction around the completion of meaningful communicative tasks rather than the pre-teaching of discrete linguistic items. This paper examines TBLL as a theoretically grounded and practice-oriented framework for philological university contexts where learners require advanced academic English, disciplinary literacy, and interactional competence. Drawing on major positions in second language acquisition, the study conceptualizes tasks as goal-directed activities that create conditions for authentic language use, attention to form, and strategic competence through negotiation of meaning, feedback, and post-task reflection. Particular attention is paid to implementation in English-medium philological programs, including curriculum alignment, assessment validity, and the balance between fluency development and accuracy-oriented work. The paper also considers contextual variables typical of higher education settings such as large classes, limited contact hours, mixed proficiency groups, and exam-driven expectations, and proposes principled adaptations to preserve task authenticity while ensuring measurable outcomes. The analysis argues that TBLL, when supported by careful task design and transparent assessment criteria, can strengthen students’ communicative performance, academic discourse skills, and learner autonomy in university-level English education.
Keywords: Task-based language learning; task cycle; communicative competence; focus on form; interaction; negotiation of meaning; learner autonomy; academic English; performance assessment; syllabus design